Innovation and Emerging Roles of Populus trichocarpa TEOSINTE BRANCHED1/CYCLOIDEA/PROLIFERATING CELL FACTOR Transcription Factors in Abiotic Stresses by Whole-Genome Duplication - Wang, Shuo; Shen, Yirong; Guo, Liangyu; Tan, Lingling; Ye, Xiaoxue; Yang, Yanmei; Zhao, Xijuan; Nie, Yuqi; Deng, Deyin; Liu, Shenkui; Wu, Wenwu (Frontiers in Plant Science, 2022)
The Teosinte branched1/Cincinnata/Proliferating cell factor (TCP) family proteins are plant-specific transcription factors that have been well-acknowledged for designing the architectures of plant branch, shoot, and inflorescence. However, evidence for their innovation and emerging role in abiotic stress has been lacking. Here, we identified a total of 36 TCP genes in Populus trichocarpa, 50% more than that in Arabidopsis (i.e. 24). Comparative intra-genomes showed such significant innovation was mainly due to the most recent Whole Genome Duplication (rWGD) in Populus lineage around Cretaceous–Paleogene (K–Pg) boundary after the divergence from Arabidopsis. Transcriptome analysis showed the expressions of PtrTCP genes varied among leaf, stem, and root, and they could also be elaborately regulated by abiotic stresses (e.g. cold and salt). Moreover, co-expression network identified a cold-associated regulatory module including PtrTCP31, PtrTCP10, and PtrTCP36. Of them, PtrTCP10 was rWGD-duplicated from PtrTCP31 and evolved a strong capability of cold induction, which might suggest a neofunctionalization of PtrTCP genes and contribute to the adaptation of Populus lineage during the Cenozoic global cooling. Evidentially, overexpression of PtrTCP10 into Arabidopsis increased freezing tolerance and salt susceptibility. Integrating co-expression network and cis-regulatory element analysis confirmed PtrTCP10 can regulate the well-known cold- and salt-relevant genes (e.g., ZAT10, GolS2, and SOS1), proving that PtrTCP10 is an evolutionary innovation in P. trichocarpa response to environmental changes. Altogether, our results provide evidence of the rWGD in P. trichocarpa responsible for the innovation of PtrTCP genes and their emerging roles in environmental stresses.